A Stiff and Healable Polymer Based on Dynamic-Covalent Boroxine Bonds - Lai, Jian-Cheng; Mei, Jin-Feng; Jia, Xiao-Yong; Li, Cheng-Hui; You, Xiao-Zeng; Bao, Zhenan (Advanced materials (Weinheim), 2016)
A stiff and healable polymer is obtained by using the dynamic‐covalent boroxine bond to crosslink PDMS chain into 3D networks. The as‐prepared polymer is very strong and stiff, and can bear a load of more than 450 times its weight. When damaged, it can be completely healed upon heating after wetting.